Analisis Kesediaan Membayar WTP (Willingness To Pay) Konsumen terhadap Berbagai Jenis Beras Organik di Kota Denpasar (Studi Kasus Toko Satvika Bhoga Sanur) - PUTU PUTRI KUSUMAWICITRA; NI LUH PRIMA KEMALA DEWI; I GUSTI AYU AGUNG LIES ANGGRENI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Analysis of Consumer Willingness to Pay for Various Types of Organic Rice in Denpasar City (Case Study at Satvika Bhoga Shop, Sanur) Currently, the need for organic rice is increasing along with changes in people's lifestyles that are healthier. The relatively expensive price of organic rice triggers consumer attraction that forms the segmentation of the organic rice market and consumer behavior in buying or paying for organic food products above the selling price of non-organic food. This study aims to describe consumer market segmentation, analyze consumers' willingness to pay for organic rice and analyze the factors that influence consumers' willingness to pay for organic rice. Analysis of the data used is descriptive analysis, Contingent Valuation Method dan Structural Equation Model-Partial Least Square. The sample in this study were 150 respondents who are consumers of Satvika Bhoga Shop in Sanur. The results showed that the consumer market segmentation in demographic segmentation is more likely to make a major contribution in determining the value of Willingness to Pay. Somya Pertiwi Red Organic Rice is the most popular with an average WTP value of Rp6.720 per kg. The variables of income, product quality, product price, product safety and lifestyle have a positive and significant effect on Willingness to Pay for various types of organic rice at the Satvika Bhoga Shop in Sanur. Based on the original sample value, the research shows that the factor that most influences Willingness to Pay is product security.